CONFIGURATION OF A SIMULTANEOUS-SEPARATE GENERAL ELECTION SYSTEM TO STRENGTHEN THE CHARACTER OF AN INCLUSIVE GOVERNMENT SYSTEM IN INDONESIA - Satriansyah Den Retno Wardana; Eka N.A.M. Sihombing; Tengku Erwinsyahbana (Universitas Muhammadiyah Tangerang, 2023)
The government system essentially examines the relationship between legislative and executive institutions. On the other hand, the concept of a government system can also be related to the form of vertical relationship between the central government and regional governments. Problem formulations for this journal are; What is the character of the strengthening of the government system both at the central and regional levels resulting from the simultaneous general election system in Indonesia? What are the theories and concepts of the government system and general election system in Indonesia? a quo regional head election in Indonesia? This research is normative legal research accompanied by supporting data. The research data was collected through literature study. The analysis was carried out using qualitative methods. Based on the research results, it is concluded that: First, the government system is the concept of legislative and executive relations in carrying out their functions and duties. There are various types of systems such as presidential systems, parliamentary systems and mixed systems. In the presidential system used in Indonesia, there are systemic weaknesses in the form of fixed term features, dual democratic legitimacy, the possibility of the emergence of divided government and the use of multiparty features. Second, the configuration of the simultaneous general election system and the regional head election system can be seen that the presidential general election system uses a simultaneity feature, a presidential threshold of 20%, and uses a majority-runoff system with a distribution of votes in certain areas. Third, the implementation of simultaneous elections and a quo regional heads has not shown any significant strengthening of the government system. Strengthening of the presidential system only occurred in terms of the number of candidates competing, and the majority run-off system did not show any strengthening.